Potential of Therapeutic Curculigo latifolia Extracts on Alloxan-induced Diabetes in a Male Mus muscullus - Haryanto, Haryanto; Sutandi, Agus; Kusumawati, Eni; Nurhayati, Sari; Fitri, Fadillya Maulidilla; Nafsi, Ginan; Nuraeni, Sri Wahyuni (Biosaintifika: Journal of Biology & Biology Education, 2023)
Curculigo latifolia is a herbaceous plant that is abundant on the islands of Java, Sumatra and Kalimantan. C. latifolia has not been well explored. The research to determine the phytochemical content of C. latifolia, to analyze the organoleptic sweetness level of C. latifolia fruit and to analyze the anti-diabetic potential of C. latifolia plant extracts on  diabetic mice. The study was conducted experimentally using  6 treatment levels and 4 replications. Prior to treatment, mice were induced hyperglycemia using alloxan 150 mg/kg WB were induced subcutaneously. The treatment being tested was oral Ethanol crude extract (ECE) for 28 days with 400 mg/kg WB, namely: G1: oral mineral water; G2: glibenclamide ; G3: ECE leaf; G4: ECE root; G5: ECE fruit and G6: ECE tree. Blood sugar levels were measured at 0, 7, 14, 21 and 28 days after oral ECE. Therefore, respondents stated that after consuming the fruit, they had a sweet-tasting and taste-modifying mineral water with a strength of 82.40 ± 8.36%, but the fruit extract did not show any sweet-tasting and taste-modifying. ANOVA results showed that oral ECE administration had a significant effect low on blood sugar levels. the HSD test was carried out with a 95% confidence level. ECE C. latifolia showed positive results on the tests of flavonoids, phenolics, saponins, alkaloids, triterpenoids and tannins. G4 was effective in reducing sugar levels after short time and  G5 for 28 days (long time). C. latifolia have pharmacology effects to lower sugar levels and has taste modifying to sweetness.